Case Study: County-Level Responses to the Opioid Crisis in Northern Kentucky. Issue 2 (June 2018) - Johnson, Quentin
This article highlights local government responses to the opioid crisis in Northern Kentucky through a series of interviews with county-level officials. The author's discussions with civic leaders reflect the challenges faced by local communities and the new approaches implemented to stem the epidemic.